Axial loads on implant-supported partial fixed prostheses for external and internal hex connections and machined and plastic copings: strain gauge analysis - Oliveira de Vasconcellos, Luis Gustavo [UNESP]; Kojima, Alberto Noriyuki [UNESP]; Nishioka, Renato Sussumu [UNESP]; Reis de Vasconcellos, Luana Marotta [UNESP]; Balducci, Ivan [UNESP] (Allen Press Inc, 2015)
The aim of this in vitro study was to use strain gauge (SG) analysis to compare the effects of the implant-abutment joint, the coping, and the location of load on strain distribution in the bone around implants supporting 3-unit fixed partial prostheses. Three external hexagon (EH) implants and 3 internal hexagon (IH) implants were inserted into 2 polyurethane blocks. Microunit abutments were screwed onto their respective implant groups. Machined cobalt-chromium copings and plastic copings were screwed onto the abutments, which received standard wax patterns. The wax patterns were cast in a cobalt-chromium alloy (n = 5): group 1 = EH/machined. group 2 = EH/plastic, group 3 = IH/machined, and group 4 = IH/plastic. Four SGs were bonded onto the surface of the block tangentially to the implants. Each metallic structure was screwed onto the abutments and an axial load of 30 kg was applied at 5 predetermined points. The magnitude of microstrain on each SG was recorded in units of microstrain (mu epsilon). The data were analyzed using 3-factor repeated measures analysis of variance and a Tukey test (alpha = 0.05). The results showed statistically significant differences for the type of implant-abutment joint, loading point, and interaction at the implant-abutment joint/loading point. The IH connection showed higher microstrain values than the EH connection. It was concluded that the type of coping did not interfere in the magnitude of microstrain, but the implant/abutment joint and axial loading location influenced this magnitude.
Keywords: Biomechanics; Dental implants; Dental prosthesis; Implant-supported dental prosthesis